2023
DOI: 10.52053/jpap.v4i2.158
|View full text |Cite
|
Sign up to set email alerts
|

Grit and Academic Burnout among Accountancy Students in Pakistan: Mediating Role of Academic Resilience

Abstract: The intended focus of this study on the accountancy students in Pakistan is due to the pressure to excel academically combined with a heavy workload, high academic pressure and frequent examinations leads to high levels of academic burnout among accountancy students. The present study was carried out to identify the relationship between grit, academic resilience and academic burnout among accountancy students. Data was comprised of 400 accountancy students of which 202 were males and 198 females who were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…We can expect a determined student to be more persistent in the face of difficulties after such interventions from their parents. Research has reported that the more gritty students are determined to continue pushing forward to achieve their goals over long periods, rather than giving up immediately (Khan et al, 2023;Wicaksono et al, 2023). Students with high levels of grit can demonstrate success and determination in their studies despite difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…We can expect a determined student to be more persistent in the face of difficulties after such interventions from their parents. Research has reported that the more gritty students are determined to continue pushing forward to achieve their goals over long periods, rather than giving up immediately (Khan et al, 2023;Wicaksono et al, 2023). Students with high levels of grit can demonstrate success and determination in their studies despite difficulties.…”
Section: Discussionmentioning
confidence: 99%